Scott Pilgrim vs the world: Scott Pilgrim # 2 - O'Malley, Bryan Lee (Portland, OR : Oni Press, 2012)
Scott gets ready to fight Ramona's second evil ex-boyfriend, but things get more complicated when Scott's exes show up.
Reprint. Originally published: 2005.
Keywords: Graphic novels